Increased preparation time reduces, but does not abolish, action history bias of saccadic eye movements - Reuter, E.M.; Marinovic, Welber; Welsh, T.N.; Carroll, T.J. (AMER PHYSIOLOGICAL SOC, 2019)
The characteristics of movements are strongly history-dependent. Marinovic et al. (Marinovic W, Poh E, de Rugy A, Carroll TJ. eLife 6: e26713, 2017) showed that past experience influences the execution of limb movements through a combination of temporally stable processes that are strictly use dependent and dynamically evolving and contextdependent processes that reflect prediction of future actions. Here we tested the basis of history-dependent biases for multiple spatiotemporal features of saccadic eye movements under two preparation time conditions (long and short). Twenty people performed saccades to visual targets. To prompt context-specific expectations of most likely target locations, 1 of 12 potential target locations was specified on ~85% of the trials and each remaining target was presented on ~1% trials. In long preparation trials participants were shown the location of the next target 1 s before its presentation onset, whereas in short preparation trials each target was first specified as the cue to move. Saccade reaction times and direction were biased by recent saccade history but according to distinct spatial tuning profiles. Biases were purely expectation related for saccadic reaction times, which increased linearly as the distance from the repeated target location increased when preparation time was short but were similar to all targets when preparation time was long. By contrast, the directions of saccades were biased toward the repeated target in both preparation time conditions, although to a lesser extent when the target location was precued (long preparation). The results suggest that saccade history affects saccade dynamics via both use- and expectationdependent mechanisms and that movement history has dissociable effects on reaction time and saccadic direction. NEW & NOTEWORTHY The characteristics of our movements are influenced not only by concurrent sensory inputs but also by how we have moved in the past. For limb movements, history effects involve both use-dependent processes due strictly to movement repetition and processes that reflect prediction of future actions. Here we show that saccade history also affects saccade dynamics via use- and expectation- dependent mechanisms but that movement history has dissociable effects on saccade reaction time and direction.